2010
DOI: 10.1038/nature09571
|View full text |Cite
|
Sign up to set email alerts
|

Lkb1 regulates cell cycle and energy metabolism in haematopoietic stem cells

Abstract: Summary Little is known about metabolic regulation in stem cells and how this modulates tissue regeneration or tumour suppression. We studied the Lkb1 tumour suppressor, and its substrate AMPK, kinases that coordinate metabolism with cell growth. Lkb1 deletion caused increased haematopoietic stem cell (HSC) division, rapid HSC depletion, and pancytopenia. HSCs depended more acutely on Lkb1 for cell cycle regulation and survival than many other haematopoietic cells. HSC depletion did not depend on mTOR activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
443
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(477 citation statements)
references
References 45 publications
23
443
2
Order By: Relevance
“…One major observation in this study is that a physiological trigger of autophagy, such as nutrient deprivation, is able to induce DNA damage through the generation of ROS. Genotoxic stress has been reported to repress mTOR in response to oxidative stress caused by ROS through a cytoplasmic signaling node for LKB1/AMPK/TSC2 activation in response to oxidative stress [31]. The COMET assay and histone γ-H2AX accumulation confirmed the persistence of damaged DNA and the level of initial damage corresponded with the cell's ability to initiate autophagy.…”
Section: Discussionmentioning
confidence: 94%
“…One major observation in this study is that a physiological trigger of autophagy, such as nutrient deprivation, is able to induce DNA damage through the generation of ROS. Genotoxic stress has been reported to repress mTOR in response to oxidative stress caused by ROS through a cytoplasmic signaling node for LKB1/AMPK/TSC2 activation in response to oxidative stress [31]. The COMET assay and histone γ-H2AX accumulation confirmed the persistence of damaged DNA and the level of initial damage corresponded with the cell's ability to initiate autophagy.…”
Section: Discussionmentioning
confidence: 94%
“…This general theme has also been expanded by three recent studies in which the tumor suppressor and metabolic regulator LKB1 was shown to regulate HSC quiescence (51)(52)(53). In the absence of LKB1, stem cells appeared to proliferate initially, giving rise to increased progenitor cell number.…”
Section: Energy Metabolism Mitochondria and Stem Cellsmentioning
confidence: 93%
“…However, targeting liver kinase B1 (LKB1) in the beta cell for the treatment of diabetes would be undesirable as knockout of Lkb1 in adult mice has a deleterious effect on haematopoietic stem cell maturation [20][21][22]. We and others have identified non-overlapping functions in beta cells for LKB1 targets, including MAP/microtubule affinityregulating kinase 2 (MARK2), salt-inducible kinase 2 (SIK2), brain-specific kinase 2 (BRSK2) as well as AMPactivated protein kinase (AMPK) itself [19,[23][24][25][26][27][28], underscoring the potential for identifying the minimal target(s) of LKB1 responsible for enhancing insulin secretion.…”
Section: Introductionmentioning
confidence: 99%